2022
DOI: 10.1137/21m1434581
|View full text |Cite
|
Sign up to set email alerts
|

Global Well-Posedness of the KdV Equation on a Star-Shaped Network and Stabilization by Saturated Controllers

Abstract: In this work, we deal with the global well-posedness and stability of the linear and nonlinear Korteweg-de Vries equations on a finite star-shaped network by acting with saturated controls. We obtain the global well-posedness by using the Kato smoothing property for the linear case and then using some estimates and a fixed point argument we deal with the nonlinear system.Finally, we obtain the exponential stability using two different kinds of saturation by proving an observability inequality via a contradicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In Menzala, Vasconcellos and Zuazua (2002) the authors showed that if the length 𝐿 is critical, an internal damping allows the exponential stability. This idea was then applied in several works for instance Pazoto (2005); Linares and Pazoto (2009); Parada, Crépeau and Prieur (2022b). We also refer to Cerpa (2014); Rosier and Zhang (2009) for a complete introduction about control of KdV equation.…”
Section: Introductionmentioning
confidence: 99%
“…In Menzala, Vasconcellos and Zuazua (2002) the authors showed that if the length 𝐿 is critical, an internal damping allows the exponential stability. This idea was then applied in several works for instance Pazoto (2005); Linares and Pazoto (2009); Parada, Crépeau and Prieur (2022b). We also refer to Cerpa (2014); Rosier and Zhang (2009) for a complete introduction about control of KdV equation.…”
Section: Introductionmentioning
confidence: 99%